1989
DOI: 10.1038/bjc.1989.55
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of conjunctival melanomas in relation to histopathological features

Abstract: Summary Twenty-six patients (age 29-85 years) with primary malignant melanoma of the conjunctiva were analysed for usefulness of various histopathological and immunohistochemical features of the primary, recurrent and metastatic tumours in evaluating their prognosis. The mean follow-up time was 5.5 years, ranging from 8 months to 17 years. Eight patients developed metastases and seven have died. The mean time from diagnosis to death due to metastasis was 3.8 years (range 1-6 years). The site of the primary tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…Patients with multifocal tumors, orbital invasion, recurrent disease, and involvement of the caruncle, plica semilunaris, eyelid margins, and the palpebral and forniceal conjunctiva have a worse prognosis for survival. 1,5,16,[53][54][55][56][57] The mortality rate has been shown to be approximately equal in patients with conjunctival melanoma in association with and without PAM with atypia. 13,16 Histopathologic findings associated with a poor prognosis include a tumor thickness of greater than 0.8 mm (in contrast to 1.5 mm or 2 mm in different studies) and involvement of the surgical margin.…”
Section: Prognostic Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with multifocal tumors, orbital invasion, recurrent disease, and involvement of the caruncle, plica semilunaris, eyelid margins, and the palpebral and forniceal conjunctiva have a worse prognosis for survival. 1,5,16,[53][54][55][56][57] The mortality rate has been shown to be approximately equal in patients with conjunctival melanoma in association with and without PAM with atypia. 13,16 Histopathologic findings associated with a poor prognosis include a tumor thickness of greater than 0.8 mm (in contrast to 1.5 mm or 2 mm in different studies) and involvement of the surgical margin.…”
Section: Prognostic Featuresmentioning
confidence: 99%
“…13,16 Histopathologic findings associated with a poor prognosis include a tumor thickness of greater than 0.8 mm (in contrast to 1.5 mm or 2 mm in different studies) and involvement of the surgical margin. 1,5,12,16,[53][54][55][56][57] Findings indicating poor prognosis include presence of a dominant pagetoid or melanoma in situ growth pattern, PAM sine pigmento, lymphatic or vascular invasion, presence of epithelioid cells, and 5 or more mitoses per 10 high-power fields. 5,8,16 Patients with in-transit metastases (regional periocular metastases), which may be identified clinically (Fig 9) and confirmed histologically, also have a poor prognosis, with the subsequent development of systemic metastases in most of these cases.…”
Section: Prognostic Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies prognostic variables such as age, tumour size, location, invasion into the sclera or optic nerve, blind eye, cell type, rupture of Bruch's membrane and extrascleral extension of the tumour were found to predict survival in patients with uveal melanomas (Callender et al, 1941;Raivio, 1977;Affeldt et al, 1980;Pach et al, 1986;Hungerford, 1989;Gamel et al, 1992). To some extent this was also the case with conjunctival melanomas (Fuchs et al, 1989).…”
mentioning
confidence: 99%
“…In earlier studies prognostic variables such as age, tumour size, location, invasion into the sclera or optic nerve, blind eye, cell type, rupture of Bruch's membrane and extrascleral extension of the tumour were found to predict survival in patients with uveal melanomas (Callender et al, 1941; Raivio, 1977;Affeldt et al, 1980;Pach et al, 1986;Hungerford, 1989;Gamel et al, 1992). To some extent this was also the case with conjunctival melanomas (Fuchs et al, 1989 entered, McLean and Gamel (1988) found that the chi-square value for DNA amount in the cell dropped to a nonsignificant level. Rennie et al (1989) measured the sum of S and G2/M phases in 19 fresh uveal melanomas and found for diploid tumours that spindle cell neoplasms had lower cell turnover rates than epithelioid cells.…”
mentioning
confidence: 99%